2018
DOI: 10.1007/s12603-017-0937-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of food portion size estimation by older adults, young adults and nutritionists

Abstract: Abstract:Objectives: To investigate the ability of older adults, younger adults and nutritionists to assess portion size using traditional methods versus a computer-based method. This was to inform the development of a novel dietary assessment method for older adults "The NANA system". Design: Older and younger adults assessed the portion size of self-served portions of foods from a buffet style set up using traditional and computerised portion size assessment aids. Nutritionists assessed the portion size of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…The high work commitment and time constraint may have caused a high drop out among the recruited nutrition professionals. This response rate, however, is higher than a previous study on nutritionists [ 18 ], and the sample size seems to be larger than the typical sample size (10 to 25 participants) presented in previous nutrition estimation studies conducted among registered nutritionists or dietitians [ 15 , 18 , 20 ]. We acknowledge that our modest sample size may have limited statistical power to detect small weight differences for some food items.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The high work commitment and time constraint may have caused a high drop out among the recruited nutrition professionals. This response rate, however, is higher than a previous study on nutritionists [ 18 ], and the sample size seems to be larger than the typical sample size (10 to 25 participants) presented in previous nutrition estimation studies conducted among registered nutritionists or dietitians [ 15 , 18 , 20 ]. We acknowledge that our modest sample size may have limited statistical power to detect small weight differences for some food items.…”
Section: Discussionmentioning
confidence: 56%
“…Rice, as the staple for Malaysians, is the common feature in all meals and thus often estimated with accuracy in diet records by the nutrition professionals. The consistent shapes and cuts of foods could also help in accurate portion size estimation of fruits [ 15 , 35 , 39 ]. Raw vegetables (e.g., cucumber, carrots, bean sprouts) were significantly under-estimated, while drinks and chicken were consistently over-estimated in both images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it was concluded that nutrition students need more training, in order to quantify the portion size more accurately. Lastly, a comparison study that was implemented between older adults, young adults, and nutritionists regarding portion size estimation, showed that the nutritionists achieved more accurate results when compared to the other groups [ 27 ]. In the current study, we compared the visual estimation of dietitians with the GTR and showed that food items, such as pasta, rice, and chips are difficult to estimate, which corroborates previous observations [ 28 ].…”
Section: Discussionmentioning
confidence: 99%